Informal caregivers' needs on discharge from the spinal cord unit: analysis of perceptions and lived experiences. Issue 2 (16th January 2016) - Conti, Alessio; Garrino, Lorenza; Montanari, Paola; Dimonte, Valerio
Abstract: Purpose : Spinal cord injuries (SCI) are one of the most complex and disabling diseases, implying severe consequences on aspects of life of people affected by SCI and their caregivers. The aim of our study was to explore the situation of informal caregivers of persons with SCI when discharged home from a SCI Unit, in relation to needs, emotional experiences, difficulties and subsequent reactions to discharge. Methods : A purposive sample of 11 caregivers were interviewed on patients' discharge home from the Spinal Injury Care Unit and at 6 months. The semi-structured interviews were analyzed using a qualitative phenomenological methodology as described by Giorgi. Results : Five main themes emerged from the caregivers' experiences including their implicit and explicit needs. Problems concerning communication with healthcare professionals and the need for an adequate multidisciplinary taking charge of caregivers in order to support their new role emerged within all the themes. Conclusions : Results suggest that greater caregiver involvement in the rehabilitation process and their preparation for discharge are required. Communication with healthcare professionals needs to be enhanced. It would be useful to organize follow-up visits after discharge to assess intervention effectiveness. Implications for Rehabilitation: Understanding the importance of discharge from the spinal cord unit as a meaningful step in the rehabilitation path for both patients and their informal caregivers. Orientating healthcare professionals towards a better caregiver involvement during the rehabilitation process. Promoting rehabilitation interventions addressed to the patients and their caregivers concerning supportive communication strategies as well as providing meaningful information, psychological and social support, educational intervention besides the physical aspects of care. Understanding SCI survivors caregivers' needs can assist healthcare professionals in planning and improving taking charge of this core aspect of nursing care.